MicroRNAs as Factors in Bidirectional Crosstalk Between Mitochondria and the Nucleus During Cellular Senescence - Giordani, Chiara; Silvestrini, Andrea; Giuliani, Angelica; Olivieri, Fabiola; Rippo, Maria Rita (Frontiers in Physiology, 2021)
Mitochondria are essential organelles that generate most of the chemical energy to power the cell through ATP production, thus regulating cell homeostasis. Although mitochondria have their own independent genome, most of the mitochondrial proteins are encoded by nuclear genes. An extensive bidirectional communication network between mitochondria and the nucleus has been discovered, thus making them semi-autonomous organelles. The nucleus-to-mitochondria signaling pathway, called Anterograde Signaling Pathway can be deduced, since the majority of mitochondrial proteins are encoded in the nucleus, less is known about the opposite pathway, the so-called mitochondria-to-nucleus retrograde (RTG) signaling pathway. Several studies have demonstrated that non-coding RNAs (ncRNAs) are essential “messengers” of this communication between the nucleus and the mitochondria and that they might have a central role in the coordination of important mitochondrial biological processes. In particular, the finding of numerous miRNAs in mitochondria, also known as mitomiRs, enabled insights into their role in mitochondrial gene transcription. MitomiRs could act as important mediators of this complex crosstalk between the nucleus and the mitochondria. Mitochondrial homeostasis is critical for the physiological processes of the cell. Disruption at any stage in their metabolism, dynamics and bioenergetics could lead to the production of considerable amounts of reactive oxygen species (ROS) and increased mitochondrial permeability, which are among the hallmarks of cellular senescence. Extensive changes in mitomiR expression and distribution have been demonstrated in senescent cells, those could possibly lead to an alteration in mitochondrial homeostasis. Here, we discuss the emerging putative roles of mitomiRs in the bidirectional communication pathways between mitochondria and the nucleus, with a focus on the senescence-associated mitomiRs.